2018
DOI: 10.2147/nrr.s148855
|View full text |Cite
|
Sign up to set email alerts
|

The Mental Capacity Act: 10 years on – the key learning areas for healthcare professionals

Abstract: The Mental Capacity Act (MCA) became statute law in England and Wales from October 2007 and was described as a visionary piece of legislation for its time, which had the potential to give people a voice and an opportunity to be heard. However, 10 years on, the Act is not being utilized in the UK as was intended. A scrutiny report published by the House of Lords in 2014 1 identified that the MCA was not embedded into the everyday practice of health care professionals due to the lack of knowledge, understanding,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
(63 reference statements)
1
3
0
Order By: Relevance
“…The findings also indicate that professionals felt more confident about their ability to assess capacity when they used the MCAST and they associated their feelings of increased confidence with specific benefits provided by the toolkit. This is a positive outcome because professionals have reported that they lack confidence in their ability to assess capacity, particularly for certain patient groups (e.g., people with communication difficulties) [17,31]. Our finding is consistent with the results of a qualitative investigation of social care professionals' experiences of capacity assessment; these professionals also associated increased feelings of confidence with the use of capacity assessment resources such as documentation proformas [32].…”
Section: Discussionsupporting
confidence: 84%
“…The findings also indicate that professionals felt more confident about their ability to assess capacity when they used the MCAST and they associated their feelings of increased confidence with specific benefits provided by the toolkit. This is a positive outcome because professionals have reported that they lack confidence in their ability to assess capacity, particularly for certain patient groups (e.g., people with communication difficulties) [17,31]. Our finding is consistent with the results of a qualitative investigation of social care professionals' experiences of capacity assessment; these professionals also associated increased feelings of confidence with the use of capacity assessment resources such as documentation proformas [32].…”
Section: Discussionsupporting
confidence: 84%
“…Previous reviews have focused on MCA provisions in relation to health and social care practice [ 22 , 43 ] and clinical trials of medicines, which is governed by different legislation (The Medicines for Human Use Clinical Trials Regulations [ 16 ]. Provisions for intrusive research under the MCA have been criticised for a lack of clarity leading to variable interpretations [ 21 , 44 , 45 ]. Considering these challenges, the aim of this systematic review was to develop an understanding of how adults with CDD have been included and accommodated within research studies within England and Wales following the implementation of the MCA, 2005.…”
Section: Introductionmentioning
confidence: 99%
“…However, the assessment of decision-making capacity may not always be a matter of black and white, which has been voiced by critics in England and Wales. 42 For instance, what level of decision-making capacity people should have in order to make decisions about their own health is difficult to assess. 42 43 In addition, these difficulties are partly related to the fact that many patients have decision-making capacity regarding certain decisions but not others.…”
Section: Respecting Autonomy (Only Restraining Those With Insufficien...mentioning
confidence: 99%